Methodological foundations of accounting of electronic money and payments in modern conditions - Гура, Надія Олександрівна; Чапля, Павло Вікторович (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . In the current context of the rapid digitalization of financial processes and the accelerated development of information technologies, the issue of methodological foundations for the accounting of electronic money and payments is becoming increasingly relevant. This contributes to enhancing the efficiency of financial management, improving the control and audit systems and strengthening user trust in electronic money. M e t h o d s . The dialectical method was applied to study the development of electronic money and payments, while a systematic approach was used to determine the methodological approaches to accounting. The analysis of existing types of electronic money and their legal and accounting frameworks was conducted using methods of analysis and synthesis, induction and deduction. The accounting model was developed through the modeling method. The analogy method was used to compare digital and non-digital money, cashless and electronic payments, while the double-entry method was employed to form accounting entries for electronic payment transactions. R e s u l ts. Based on the analysis of the essence and types of electronic money, a new definition was proposed, and the necessity of clearly distinguishing between different types of electronic money, such as funds in e-wallets, payment cards, and cryptocurrencies, was substantiated. Each of these has its own characteristics and requires an individual approach to accounting. Taking into account legislative approaches and scholarly proposals, sub-accounts for accounting for various types of electronic money were suggested. Accounting entries for electronic payments were provided in settlements with different debtors and creditors under various payment conditions and using different types of electronic money. Using the proposed sub-accounts, an accounting model for reflecting electronic money and payments was constructed. Attention was drawn to the importance of recognizing and valuing electronic money based on current market data, developing approaches to documenting electronic money transactions, and ensuring their control as a key component of ensuring transparency in accounting processes and compliance with legal requirements. C o n c l u s i o n s . The methodology for accounting for electronic money and payments proposed by the authors will contribute to the improvement of accounting support for these operations and control measures in the context of using information technologies.

В с т у п . У сучасних умовах швидкої цифровізації фінансових процесів та стрімкого розвитку інформаційних технологій питання методичних основ обліку електронних грошей і платежів набувають особливої актуальності, що сприятиме підвищенню ефективності фінансового менеджменту, удосконаленню системи контролю та аудиту, а також зміцненню довіри з боку користувачів електронних грошей. М е т о д и . Для розгляду розвитку електронних грошей і платежів застосовано діалектичний метод, для визначення методологічних підходів до їх обліку – системний підхід. Аналіз існуючих видів електронних грошей, їх законодавчого та облікового забезпечення здійснено на основі методів аналізу та синтезу, індукції та дедукції, Облікову модель побудовано за допомогою методу моделювання. Метод аналогій застосовано для порівняння цифрових і нецифрових грошей, безготівкових і електронних платежів, метод подвійного запису – для формування бухгалтерських проведень з обліку електронних платежів. Р е з у л ь т а т и . На основі розкриття сутності і видів електронних грошей запропоновано їх власне визначення, обґрунтовано необхідність чіткого розмежування між різними видами електронних грошей, такими як кошти на електронних гаманцях та платіжних картках, криптовалюти, кожен з яких має свої особливості та потребує індивідуального підходу до обліку. З урахуванням законодавчих підходів і пропозицій науковців запропоновано субрахунки для обліку різних видів електронних грошей. Наведено бухгалтерські проведення з обліку електронних платежів під час розрахунків з різними дебіторами і кредиторами за різних умов платежів і використання різних видів електронних грошей. З використанням запропонованих субрахунків побудовано облікову модель відображення електронних грошей і платежів. Акцентовано увагу на важливості визнання та оцінки електронних грошей на основі актуальних ринкових даних, розробки підходів до документування операцій з електронними грошима та їх контролю як важливої складової забезпечення прозорості облікових процесів та відповідності вимогам законодавства. В и с н о в к и . Запропонована авторами методика обліку електронних грошей та платежів сприятиме вдосконаленню облікового забезпечення цих операцій і контрольних заходів в умовах використання інформаційних технологій.
Методологічні основи обліку електронних грошей і платежів у сучасних умовах
Keywords: електронні гроші; облік; електронні платежі; облікова модель; субрахунки; криптовалюта; M41; електронні гроші; electronic money; accounting; electronic payments; accounting model; subaccounts; cryptocurrency